2003
DOI: 10.1249/01.mss.0000069748.02525.b2
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Physical Activity via Pedometry in Elementary Physical Education

Abstract: Data supports the use of pedometry steps per minute values as an accurate indicator of MVPA. Pedometry demonstrates promise as a viable large-scale surveillance instrument for measuring MVPA in physical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
97
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 20 publications
13
97
0
8
Order By: Relevance
“…An interval of 52-64 was found to be diagnostically efficient in quantifying 33.33% MVPA among lower secondary PE students aged 12-14 years. This was similar to previous studies that collectively found 58-65 steps/min among youth aged 6.9-13.8 years (Scruggs et al, 2003;2005). A steps/min interval of 73-76 corresponding to 50% MVPA did not align with previous research previously identified 79-86 among youth of a similar age and older (12.9 -16.5 years in Scruggs 2007a; Scruggs et al,…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…An interval of 52-64 was found to be diagnostically efficient in quantifying 33.33% MVPA among lower secondary PE students aged 12-14 years. This was similar to previous studies that collectively found 58-65 steps/min among youth aged 6.9-13.8 years (Scruggs et al, 2003;2005). A steps/min interval of 73-76 corresponding to 50% MVPA did not align with previous research previously identified 79-86 among youth of a similar age and older (12.9 -16.5 years in Scruggs 2007a; Scruggs et al,…”
Section: Resultssupporting
confidence: 92%
“…A linear regression equation found a similar result at 58 steps/min to predict 33.33% MVPA time. Four previous studies identified similar steps/min intervals with 58-65 steps/min among samples ranging from M = 6.9-13.8 years (Scruggs et al, 2003;2005;2007b) compared to M = 14.1 years in the present study. Scruggs (2013b) analysed data from previous studies for the 33.33% MVPA criteria and identified 59.5-61.8 steps/min as being optimal for children in 1 st to 7 th grade PE (mean age for samples ranged from 6.9-13.8 years).…”
Section: Pedometer Step Per Minute Guidelines Corresponding To Spendisupporting
confidence: 77%
See 2 more Smart Citations
“…These pedometers are considered most accurate for research purposes (Schneider et al, 2004). To follow the recommendations specified in various studies by Scruggs and colleagues (Scruggs, 2007a(Scruggs, , 2007b(Scruggs, , 2013a(Scruggs, , 2013bScruggs et al, 2003Scruggs et al, , 2005Scruggs et al, , 2010, all data gathered during PE lessons were adjusted to units of steps per minute to make the results comparable with other studies. For this reason the exact duration of pedometer measurement within PE lessons was recorded.…”
Section: Methodsmentioning
confidence: 99%